DNA Methylation Profile in Human Cord Blood Mononuclear Leukocytes From Term Neonates: Effects of Histological Chorioamnionitis - Fong, Gina; Gayen nee' Betal, Suhita; Murthy, Swati; Favara, Michael; Chan, Joanna S. Y.; Addya, Sankar; Shaffer, Thomas H.; Greenspan, Jay; Bhandari, Vineet; Li, Dongmei; Rahman, Irfan; Aghai, Zubair H. (Frontiers in Pediatrics, 2020)
Background: Histological chorioamnionitis (HCA) is an infection/inflammation of fetal membranes and complicates 5.2%-28.5% of all live births. Exposure to HCA can have long-term consequences including abnormal neurodevelopment and an increased risk for allergic disorders and asthma later in childhood. HCA may incite epigenetic changes, which have the potential to modulate both the immune and neurological systems as well as increase the risk of related disorders later in life. However, there is limited data on the impact of HCA on epigenetics, in particular DNA methylation, and changes to immune and neurological systems in full-term human neonates. Objective: To determine differential DNA methylation in cord blood mononuclear leukocytes from neonates exposed to HCA. Methods: Cord blood was collected from 10 term neonates (5 with HCA and 5 controls without HCA) and mononuclear leukocytes were isolated. Genome-wide DNA methylation screening was performed on Genomic DNA extracted from mononuclear leukocytes. Results: Mononuclear leukocytes from cord blood of HCA-exposed neonates showed differential DNA methylation of 68 probe sets compared to the control group (44 hypermethylated, 24 hypomethylated) with a p-value ≤ 0.0001. Several genes involved in immune modulation and nervous system development were found to be differentially methylated. Important canonical pathways as revealed by Ingenuity Pathway Analysis (IPA) were CREB Signaling in Neurons, FcγRIIB Signaling in B Lymphocytes, Cell Cycle: G1/S Checkpoint Regulation, Interleukin-1, 2, 3, 6, 8, 10, 17 and 17A signaling, p53 signaling, dopamine degradation, and serotonin degradation. The diseases and disorders picked up by IPA were nervous system development and function, neurological disease, respiratory disease, immune cell trafficking, inflammatory response, and immunological disease. Conclusions: HCA induces differential DNA methylation in cord blood mononuclear leukocytes. The differentially methylated genes may contribute to inflammatory, immunological and neurodevelopmental disorders in neonates exposed to HCA.